Disinformation Online and the Principle of Non-intervention - Czepulonis, Piotr (Polish Review of International and European Law, 2025)
Disinformation is as old as communication. Yet, its latest reincarnation in the form of so-called fake or misleading news distributed by social media provokes new questions under international law. Due to its qualitative and quantitative characteristics modern disinformation can have a debilitating impact on election processes, social order or even national security. Its growing importance from the perspective of international law has been reflected in adoption of relevant resolutions by the UN General Assembly and the Human Rights Council as well as in initiatives undertaken by states and regional organizations to address the problem of foreign disinformation campaigns. The crucial question for an international lawyer is whether a disinformation campaign may violate international law and if so which norms or principles thereof. This article will focus on the principle which seems to be of particular importance in the context of disinformation, namely the principle of non-intervention. While taking into account latest developments in the field, the text will try to clarify whether and if so under what circumstances a disinformation campaign may violate the principle. The affirmative view has been expressed by several states in their national positions on application of international law to cyberspace. The COVID-19 pandemic during which disinformation exacerbated public health crises, clearly played a role in forming at least some of these positions. The text will separately tackle two elements forming the principle of non-intervention: a) interference with a state’s internal or external affairs; and b) coercion. It will pay a particular attention to the scope of the term „coercion” in the context of information domain. Since coercion may be understood as either taking control over sovereign decisions or „extorting” expected behaviour from another state, the article will tackle both meaning of the term.